Answer: 4
Step-by-step explanation: when finding the difference you're subtracting the 2 so 8-4=4 9x^2 + 5x - 6= 8
Factoring 9x2+5x-6
The first term is, 9x2 its coefficient is 9 .
The middle term is, +5x its coefficient is 5 .
The last term, "the constant", is -6
Step-1 : Multiply the coefficient of the first term by the constant 9 • -6 = -54
Step-2 : Find two factors of -54 whose sum equals the coefficient of the middle term, which is 5 .
-54 + 1 = -53
-27 + 2 = -25
-18 + 3 = -15
-9 + 6 = -3
-6 + 9 = 3
-3 + 18 = 15
-2 + 27 = 25
-1 + 54 = 53
=8
2x^2 - 7x + 14 =4
actoring 2x2-7x+14
The first term is, 2x2 its coefficient is 2 .
The middle term is, -7x its coefficient is -7 .
The last term, "the constant", is +14
Step-1 : Multiply the coefficient of the first term by the constant 2 • 14 = 28
Step-2 : Find two factors of 28 whose sum equals the coefficient of the middle term, which is -7 .
=4